2014
DOI: 10.1179/1607845414y.0000000208
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of the hypothalamic-pituitary-adrenal axis in children with acute lymphoblastic leukemia receiving chemotherapy

Abstract: Adrenal suppression is an inevitable consequence of ALL therapy. Monitoring of cortisol levels and steroid coverage during stress is recommended, and gradual steroid tapering is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 22 publications
1
23
3
Order By: Relevance
“…A key issue is time to recovery of the HPA axis following discontinuation of glucocorticoid treatment. The percentage of patients with adrenal insufficiency following oral treatment cessation declines over time, but remains up to 40% six months following cessation (21,22,23,24,25), 20% two years following cessation (26,27,28), and 5% three years following cessation (26). This underscores the potential long-term nature of adrenal insufficiency after glucocorticoid use.…”
Section: Recovery Of the Hpa Axismentioning
confidence: 97%
“…A key issue is time to recovery of the HPA axis following discontinuation of glucocorticoid treatment. The percentage of patients with adrenal insufficiency following oral treatment cessation declines over time, but remains up to 40% six months following cessation (21,22,23,24,25), 20% two years following cessation (26,27,28), and 5% three years following cessation (26). This underscores the potential long-term nature of adrenal insufficiency after glucocorticoid use.…”
Section: Recovery Of the Hpa Axismentioning
confidence: 97%
“…It may be aggravated by co-administration of fluconazole 122 . Thus, corticosteroid replacement is indicated during the first weeks to months after cessation of corticosteroid therapy, not least during episodes of serious stress unless a stimulation test has shown a normal adrenal response 122, 123 . The duration of adrenal insufficiency has been ascribed to variants of the GR gene 124 , but formal genome-wide association analyses are lacking.…”
Section: Endocrinopathiesmentioning
confidence: 99%
“…The Cochrane review also suggests that clinicians should pay special attention to patients who have received fluconazole during their induction therapy [ 10 ]. Earlier studies have shown that fluconazole has a delaying effect on the adrenal recovery with fluconazole doses over 10 mg/kg/day [ 11 ]. This may be due to higher steroid concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…The median time to normal adrenal function in group 1 was 31 days (95% CI 28-34), 24 days in group 2 (95% CI 18-30) and 12 days in group 3 (95% CI [10][11][12][13][14]. The probability for recovery changed between days 20 and 30 for group 3, but for the other two groups the recovery was more linear with time ( Supplementary Fig.…”
Section: Factors Contributing To Full Recovery Of Hpa Axismentioning
confidence: 95%